Etika Pemilihan Ciri Non-Medis Embrio: Analisis Bioetika atas Praktik ‘Designer Baby’ dalam IVF Modern - Anggi Agustin; Anita Fitriani; Clarissa Syahnaz Aulia; Tri Cahyanto (Jurnal Pendidikan Kimia, Fisika dan Biologi, 2026)
Advances in in vitro fertilization (IVF) technology have expanded the scope of reproductive interventions, from simply addressing infertility to enabling genetic selection of embryos through preimplantation genetic testing (PGT). This advancement not only enables the detection and prevention of severe genetic diseases, but also opens up opportunities for the selection of non-medical traits such as intelligence potential, physical characteristics, or specific polygenic scores, giving rise to the phenomenon of “designer babies.” This development presents complex bioethical issues related to human dignity, social justice, biological safety, and the right of children to have an open future. This paper aims to analyze the ethical issues of selecting non-medical characteristics of embryos in modern IVF through a literature review using a biomedical ethics framework, including the principles of autonomy, beneficence, non-maleficence, and justice. The findings show that the application of technology for non-medical purposes is still fraught with scientific risks, biological uncertainties, the potential for commercialization of humans, and the threat of socio-biological inequality. This analysis emphasizes the need to restrict the use of technology to clear medical indications, increase regulation and governance, and involve the public in policy formulation. Thus, advances in reproductive technology must be accompanied by strict ethical considerations so as not to sacrifice individual dignity and the value of justice in society.